Investigation of LOY in Prostate, Pancreatic, and Colorectal Cancers in males: A case–control study. (1st December 2020) - Asim, Ambreen; Agarwal, Sarita; Avasthi, Kapil Kumar; Sureka, Sanjoy; Rastogi, Neeraj; Dean, Deepika Delsa; Mohindra, Samir
ABSTRACT: Background : LOY is associated with ageing and increase the incidence of cancers. Aims : To elucidate the role of LOY in various cancer types, namely, prostate (PRT), pancreatic (PC), and colorectal (CRC) cancers in males. Material and Methods : Fifty CRC patients [mean age = 44.58±11.2 years], fifty PRT [mean age= 60.48± 17.07 years] and fifty PC [mean age = 48.74 ±16.45 years] along with 100 healthy controls [mean age= 54.06 ±15.04 years] were recruited. DNA was isolated from peripheral blood and was subjected to multiplex QF-PCR. The Y/X ratio was calculated from the peak height. Results : The mean Y/X ratio was lower in all patients with cancers (0.875333± 0.086; p value˂ 0.0001) than in controls (1.11 ± 0.071), as well as, in CRC (0.926±0.192; p value˂0.0001), PC (0.85 ± 0.0311; p value˂0.0001) and PRT (0.85±0.122; p value˂0.0001) when calculated separately. Multivariate logistic regression analysis was used to analyze the strength of the presence of cancer prediction using the percentage of LOY and age showed that LOY (p= 0.001) is a better predictor of cancer presence than age (p= 0.359). Conclusion : LOY in blood could be a predictive biomarker in the carcinogenesis of males.